Periprosthetic knee fractures. A review of epidemiology, risk factors, diagnosis, management and outcome - Canton, Gianluca; Ratti, Chiara; Fattori, Roberto; Hoxhaj, Bramin; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Periprosthetic knee fractures incidence is gradually raising due to aging of population and increasing of total knee arthroplasties. Management of this complication represents a challenge for the orthopaedic surgeon. Aim of the present study is to critically review the recent literature about epidemiology, risk factors, diagnosis, management and outcome of periprosthetic knee fractures. Methods: A systematic search of Embase, Medline and Pubmed was performed by two reviewers who selected the eligible papers favoring studies published in the last ten years. Epidemiology, risk factors, diagnostic features, clinical management and outcome of different techniques were all reviewed. Results: 52 studies including reviews, meta-analysis, clinical and biomechanical studies were selected. Conclusions: Correct clinical management requires adequate diagnosis and evaluation of risk factors. Conservative treatment is rarely indicated. Locking plate fixation, intramedullary nailing and revision arthroplasty are all valuable treatment methods. Surgical technique should be chosen considering age and functional demand, comorbidities, fracture morphology and location, bone quality and stability of the implant. Given the correct indication all surgical treatment can lead to satisfactory clinical and radiographic results despite a relevant complication rate.